Management of cancer-related fatigue in Taiwan: an evidence-based consensus for screening, assessment and treatment. (9th November 2022) - Rau, Kun-Ming; Shun, Shiow-Ching; Hung, Shih-Hsin; Chou, Hsiu-Ling; Ho, Ching-Liang; Chao, Ta-Chung; Liu, Chun-Yu; Lien, Ching-Ting; Hong, Ming-Ying; Wu, Ching-Jung; Tsai, Li-Yun; Jane, Sui-Whi; et al.
Abstract: Background: Cancer-related fatigue is one of the most common and persistent issues experienced by cancer patients. Cancer-related fatigue is a distinct form of fatigue that is subjective, long-lasting and unalleviated by rest or sleep. Studies have shown that almost all cancer patients experience severe fatigue that disrupts the quality of life and physical function, but cancer-related fatigue remains under-addressed in clinical care, and only about half of all patients receive treatment. Methods: To increase the awareness of cancer-related fatigue and improve current management, the Taiwan Society of Cancer Palliative Medicine and the Taiwan Oncology Nursing Society convened a consensus committee to develop recommendations for the screening, assessment and treatment of cancer-related fatigue. Results: Thirteen consensus recommendations were subsequently developed based on the best available evidence and the clinical experience of committee members. Conclusions: These recommendations are expected to facilitate the standardization of cancer-related fatigue management across Taiwan and may also serve as a reference for other clinicians. Abstract : Cancer-related fatigue should be evaluated regularly, and non-pharmacological and pharmacological interventions are critically needed.